FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DI INDONESIA - LIONGI KEVIN TJAHJONO; UMAR ISSA ZUBAIDI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical information about various factors that can affects firm value. These factors are financial ratio composed of return on asset, current ratio, and acid test ratio, dividend payment ratio, financial leverage, sales growth, firm size, tangibility of asset, and firm age. The population used in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) within the research period from 2018-2020. This study used purposive sampling method as the sample collection method and analyzed using multiple regression analysis using SPSS 25 media. The research population was 634 companies, and 91 companies were taken as samples. The results of this study indicate that return on asset has a positive effect, while current ratio, acid test ratio, dividend payment ratio, financial leverage, sales growth, firm size, tangibility of asset, and firm age have no effect on firm value.